IDENTIFICATION SERVICE SYSTEM UNLOADING FISHING BOATS IN THE NATONAL FISHING PORT SIBOLGA - Kaban, Purwaningsih; Zain, Jonny; Brown, Arthur (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in 10-26 February 2016 exactly lack of season catching in the ocean fishing port Sibolga. This research aims to identify the service system unloading fishing boats and to examine the queueing model in the national fishing port Sibolga. The study was conducted using a survey method. The study was conducted by taking the primary and secondary of the data for 10 days. The variables used are the data boats arrival and the customers in the fishing port quay. Based on the result of research and discussion model the queueing system for 10 days following the model of the queue (G/G/c) : (FIFO//∞/∞). Effectiveness of costumer service process can be determined by calculate the average time spent on a customer in the system and queues, as well as calculating the odds waiters are not serving costumer. It can be seen to the average time spent in the queue subscribe about 0,0003 days for each boats and for the average time was used by boats in the system about 0,036 days for each boats and service opportunities are not serving boats by 85,9%. It can be conclude the service at the time in fishing port quay for unloading is effective less.Keywords : Unloading, Queueing model, Effectiveness